How cultural distance affects cross-border M&A performance? Evidence from overseas M&A by Chinese listed companies - Lu, Hangting (2022)
This dissertation investigates the impact of cultural distance and the interaction between cultural distance and the parent company's prior cross-border M&A experience, as well as the interaction between cultural distance and the institutional level of the host country on cross-border M&A performance by using a sample of 204 Chinese listed firms over the period 2016-2020, based on the organizational learning theory and institution-based view. The findings show that cultural distance has a negative impact on cross-border M&A performance in the short term. Further research has shown that the parent company's prior cross-border M&A experience has a positive moderating effect on the negative impact of cultural distance on cross-border M&A performance. Although the moderating effect of the institutional level of the host country on the relationship between cultural distance and cross-border M&A performance has not been proven, this dissertation contributes to the exploration of topics related to the moderating variables affecting the relationship between cultural distance and cross-border M&A.